MENINGKATKAN KETAHANAN MENULIS HURUF VOKAL MELALUI MEDIA PAPAN MAGNET BAGI ANAK TUNAGRAHITA RINGAN KELAS DII/C DI SDLBN 04 TARANTANG PAYAKUMBUH - Tri Siskom (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract: This research was conducted based on the problem found at SDLB N 04 Tarantang Payakumbuh indicating that a student with light mental retardation in class DII/C was only able to write for a minute. Being asked to write five sheets of vocal letters, the student wrote them untidily. He tended to be bored, had less concern and was easily influenced by the environment. He frequently ignored the tasks assigned. This was an experimental research which applied Single Subject Research design. This quantitative research was intended to reveal whether the intervention or treatment given affected the changes over the target behavior this research used A-B design in which A the baseline phase and B was the intervention phase. The result of the research showed that the endurace of the student to write the vocal letters by copying the model before the treatment given was very low in which he was only able to write for 1 to 4 minutes, or in average he was only able to write for 2 minutes (12,5%). In the intervention condition through  which the magnetic board used, the endurance of the student wiht light mental retardation to write improved into 4 minutes and 14 minutes, or in average he was able to write revealed that the hypothesis was accepted indicating thet the magnetic board was effective to improve the endurace of the student with light mental retardation to write in class DII/C of SDLB N 04 Tarantang Payakumbuh. Kata kunci: Tunagrahita, Ketahanan Menulis Huruf Vokal, Papan Magnet